Inflammation of The Nasal and Nasal Lateral Cavities in Allergic Rhinitis Specificity of Assessment of Clinical and Morphological Indicators - Ulmasov A.O. (Scholars Digest Publishing, 2023)
Polypous rhinosinusitis (PRS), a chronic inflammatory disease of the mucous membrane of the nasal cavity and paranasal sinuses, characterized by recurrent growth of polyps, is an urgent problem of otorhinolaryngology. This is due to the high prevalence, the tendency to increase the incidence, the complexity and relatively low effectiveness of treatment. Nasal polyposis is more or less pronounced in 2.1-4.3% of the adult population, mainly in men (2.2:1), older age groups (the average age of patients is 49.4 years) and often complicates the course of bronchial asthma.
Keywords: paranasal sinus, allergic rhinitis, morphology, assessment.